If A = ⌈ 3 ⌉ + ⌈ 4 ⌉ + ⌈ 5 ⌉ + ⋯ + ⌈ 8 3 ⌉ , find the value of 3 1 ⌈ A ⌉ .
Notation : ⌈ ⋅ ⌉ denotes the ceiling function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know that for ( n − 1 ) 2 < x ≤ n 2 , where n is a positive integer,
⌈ x ⌉ = n
For example, n = 3 , 2 2 < x ≤ 3 3 ⟹ 4 < x ≤ 9
For any value of x within this range, ⌈ x ⌉ = 3
With this, we can easily calculate the value of the expression A
What we need to do is find out the number of terms between each perfect square
⌈ 3 ⌉ = ⌈ 4 ⌉ = 2 , there are 2 terms here
⌈ 5 ⌉ = ⌈ 6 ⌉ = … = ⌈ 9 ⌉ = 3 , there are 9 − 4 = 5 terms here
⌈ 1 0 ⌉ = ⌈ 1 1 ⌉ = … = ⌈ 1 6 ⌉ = 4 , there are 1 6 − 9 = 7 terms here
⌈ 1 7 ⌉ = ⌈ 1 8 ⌉ = … = ⌈ 2 5 ⌉ = 5 , there are 2 5 − 1 6 = 9 terms here
⌈ 2 6 ⌉ = ⌈ 2 7 ⌉ = … = ⌈ 3 6 ⌉ = 6 , there are 3 6 − 2 5 = 1 1 terms here
⌈ 3 7 ⌉ = ⌈ 3 8 ⌉ = … = ⌈ 4 9 ⌉ = 7 , there are 4 9 − 3 6 = 1 3 terms here
⌈ 5 0 ⌉ = ⌈ 5 1 ⌉ = … = ⌈ 6 4 ⌉ = 8 , there are 6 4 − 4 9 = 1 5 terms here
⌈ 6 5 ⌉ = ⌈ 6 6 ⌉ = … = ⌈ 8 1 ⌉ = 9 , there are 8 1 − 6 4 = 1 7 terms here
⌈ 8 2 ⌉ = ⌈ 8 3 ⌉ = 1 0 , there are 2 terms here
Therefore,
A = ⌈ 3 ⌉ + ⌈ 4 ⌉ + ⌈ 5 ⌉ + … + ⌈ 8 3 ⌉ = 2 ( 2 ) + 3 ( 5 ) + 4 ( 7 ) + 5 ( 9 ) + 6 ( 1 1 ) + 7 ( 1 3 ) + 8 ( 1 5 ) + 9 ( 1 7 ) + 1 0 ( 2 ) = 5 4 0
We then calculate the desired answer:
3 1 ⌈ A ⌉ = 3 1 ⌈ 5 4 0 ⌉ = 3 1 ⌈ 2 3 . 2 4 ⌉ = 3 1 ( 2 4 ) = 8
Great!! Same thinking!!
I did it by brute force as well, but I grouped them up according to (9-4) (16-9) and all and finally obtained - 8 - (sum of squares from 3 sq to 8 sq) +9*81 + 20. Then I manually calculated 21, 22 and 23 square to finally reach the solution. Please don't do this, especially the first bit unless you're gonna turn it into a summation like the top comment.
Problem Loading...
Note Loading...
Set Loading...
A = 2 4 ⌈ 3 ⌉ + ⌈ 4 ⌉ + ( 9 − 4 ) 9 ⌈ 5 ⌉ + ⋯ + ⌈ 9 ⌉ + ( 1 6 − 9 ) 1 6 ⌈ 1 0 ⌉ + ⋯ + ⌈ 1 6 ⌉ + ⋯ + ( 8 1 − 6 4 ) 8 1 ⌈ 6 5 ⌉ + ⋯ + ⌈ 8 1 ⌉ + 2 1 0 0 ⌈ 8 2 ⌉ + ⌈ 8 3 ⌉ = 2 ( 2 ) + k = 3 ∑ 9 ( k 2 − ( k − 1 ) 2 ) k + 2 ( 1 0 ) = 4 + k = 3 ∑ 9 ( 2 k 2 − k ) + 2 0 = 4 + 2 × 6 9 ( 9 + 1 ) ( 2 ( 9 ) + 1 ) − 2 × 6 2 ( 2 + 1 ) ( 2 ( 2 ) + 1 ) − 2 9 ( 9 + 1 ) + 2 2 ( 2 + 1 ) + 2 0 = 4 + 5 7 0 − 1 0 − 4 5 + 3 + 2 0 = 5 4 2
Therefore, 3 1 ⌈ A ⌉ = 3 1 × 2 4 = 8 .